QUANTITATIVE AND QUALITATIVE LOSSES FROM HARVESTERS WITH RADIAL AND AXIAL THRESHING SYSTEMS DEPENDING ON GRAIN MOISTURE - Camolese, H.S.; Baio, F.H.R.; Alves, C.Z. (Revista Brasileira de Engenharia de Biossistemas, 2015)
he grain harvest is one of the main stages in the crop production cycle, mainly by being able to influence the reduction of field yield, if the harvester adjustments are not appropriate. Thus, this study aims to evaluate the qualitative and quantitative grain losses from harvesters with radial and axial threshing systems in the soybean crop, according to the grain moisture variation. Two harvesters were evaluated with two threshing systems: an axial; and another radial. The grain moisture harvested was into two conditions: within the recommended moisture; and not recommended. It was made the evaluation of the quantitative losses on the pre-harvest grain, the cutter bar, the separating and cleaning mechanism and the qualitative losses by the mechanical damage index and grains purity. The quantitative grain loss on the separating and cleaning mechanism is influenced by the threshing system, being lower by use of harvester equipped with an axial threshing, regardless of soybean grain moisture. This same threshing system also provides a higher grain purity index. The harvester equipped with radial threshing system provides higher mechanical damage index, being higher the lower grain moisture.